2008
DOI: 10.1002/jmri.21345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of regional myocardial oxygenation changes in the presence of coronary artery stenosis with balanced SSFP imaging at 3.0T: Theory and experimental evaluation in canines

Abstract: Purpose:To examine the dependence of steady-state freeprecession (SSFP) -based myocardial blood-oxygen-leveldependent (BOLD) contrast on field strength using theoretical and experimental models. Materials and Methods:Numerical simulations using a two-pool exchange model and a surgically prepared dog model were used to assess the SSFP-based myocardial BOLD signal changes at 1.5T and 3.0T. Experimental studies were performed in eight canines with pharmacological vasodilation under various levels of left circumfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 41 publications
(69 reference statements)
5
58
0
Order By: Relevance
“…Since microscopic susceptibility increases with field strength, thus making oxygenation sensitivity due to ischemic (patho) physiology more pronounced, T 2 * mapping at 7.0 T might be beneficial to address some of the BOLD sensitivity constraints reported for the assessment of regional myocardial oxygenation changes in the presence of coronary artery stenosis [121] or for the characterization of vasodilator-induced changes of myocardial oxygenation at 1.5 T and at 3.0 T [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since microscopic susceptibility increases with field strength, thus making oxygenation sensitivity due to ischemic (patho) physiology more pronounced, T 2 * mapping at 7.0 T might be beneficial to address some of the BOLD sensitivity constraints reported for the assessment of regional myocardial oxygenation changes in the presence of coronary artery stenosis [121] or for the characterization of vasodilator-induced changes of myocardial oxygenation at 1.5 T and at 3.0 T [10].…”
Section: Discussionmentioning
confidence: 99%
“…Phantom studies suggested a three-fold increase of myocardial BOLD contrast at 3.0 Tesla in comparison to 1.5 Tesla. 39 In an experimental setting the gain in myocardial BOLD contrast based on a SSFP sequence at 3.0 Tesla reached up to a 2.5-fold signal increase. 39 Favorably, the increase in myocardial BOLD signal using the abovementioned SSFP sequence was observed independently of varying coronary blood flow.…”
Section: Technical Aspects Of Bold Cmr Imagingmentioning
confidence: 99%
“…As recently reviewed, the BOLD CMR technique has been extensively validated in preclinical and clinical studies at both 1.5 and 3 T using a variety of sequences. 35 The SSFP sequence used in this study was initially validated in the canine heart at 1.5 T by Fieno et al 20 We used the higher field strength (3 T) given the limited signal-to-noise ratio between normal and deoxygenated myocardial regions at 1.5 T. 21 The BOLD measurement reproducibility in this study compares favorably with the BOLD SI measurement reproducibility demonstrated by Karamitsos et al, who used the same SSFP sequence at 3 T. 23 Myocardial Oxygenation, Epicardial and Microvascular CAD BOLD CMR technique can identify not only epicardial coronary artery stenosis, but also potentially coronary microvascular dysfunction. BOLD CMR has moderate accuracy in detecting significant CAD.…”
Section: Bold Cmr Techniquementioning
confidence: 99%
“…11 The transition from diamagnetic oxyhemoglobin to paramagnetic deoxyhemoglobin induces a change in magnetic resonance signal intensity (SI) and thereby generates oxygen-dependent contrast. 12 The BOLD technique has been validated in animal models [13][14][15][16][17][18][19][20][21] and utilized in human studies in patients with angina, CAD, syndrome X, and hypertension. [22][23][24][25][26] We utilized BOLD CMR to measure myocardial oxygenation response to stress in the CKD population as a measure of myocardial ischemia and searched for associations with renal function.…”
mentioning
confidence: 99%